Goals, relationships, information and processes in global virtual team performance. (9th November 2004) - Workman, Michael
The implementation of virtual teams is briskly increasing, particularly among transnational organisations that find global virtual teams a natural way to address their needs for global reach. Much of the research into virtual teams has been concentrated at the micro-organisational level of the individual virtual worker. This study extends the body of research to the team level by using Hofstede's (1998) GRIP model to examine culture and structuring on global virtual team performance. Specifically, Hofstede's (1998) six components, along with virtual team duration and diversity, were found to influence virtual team budget variance, schedule variance, and the number of errors created by the team.